(3TQM GdbUjOI GdHGFjIs - (3CHh GdbGSe, GdTQja GdeQJVj, Ydj Hf GdMSjf Hf ehSi, J (B436(3g` (B1044(3e(B)s
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B.. (3SCd GdSjO GdhdO (B... (3JaSjQ bUjOI CHj gGTe ESeGYjd (B... (3GdJj ChdgG(B: (3gdG hbaJ Ydi GdecGf GdeYTHs
(3BNQgG (B:s
(3BNQgG(B: (3hGdhLg GdBNQ Cf jQjO HGdcJGH GdbQBf, hdG THgI Ydi Cfg JYGdi jYde eG RGO Ydi Pdc cdg heG dG jJfGgi ef GdeYdheGJ(B. (3JeJ GdbUjOI hTQMgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 278s
(3GdPQjYI, L (B13: 169(3, L (B14: 40s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs